A retrospective study of patients complaining of nontraumatic acute abdominal pain, admitted in the emergency department of an urban hospital in China - Guanguan Luo; Qinqin Liu; Zhongxiang Zhang; Xiaoqing Jin (Emergency and Critical Care Medicine)
Abstract. Background. Nontraumatic acute abdominal pain (AAP) accounts for a large proportion of emergency department (ED) admissions. This study aimed to explore the underlying correlations among basic information, imaging examinations, and diagnoses. Methods. A total of 7453 patients complaining of AAP, admitted to the ED of Zhongnan Hospital of Wuhan University, were enrolled in this retrospective study from January 1 to December 30, 2019. We collected the following information from the patients: sex, age, date of visit, pain location, nature of pain, level of severity, imaging (computed tomography, x-ray, and ultrasound), diagnosis, and outcomes (release from the hospital, transfer to another hospital, transfer to another department, observation room, hospitalization, or death). Results. According to this study, AAP was more common in female than male. A total of 82.11% patients of AAP were in level 3 of severity, while 0.19% patients were in level 1. A total of 77.20% of the patients had undergone imaging. Swelling pain and colic are the 2 most common types of AAP. Nonspecific abdominal pain (NSAP) is the most common diagnosis. In the diagnosis of NSAP and gastroenteritis, female patients were more prevalent than male patients, but for renal colic, male patients were 3 times as many as female patients. Nonspecific abdominal pain, biliary colic, and cholecystitis are the 3 leading causes in patients 65 years or older. Nonspecific abdominal pain, renal colic, and gastroenteritis are the 3 leading causes of AAP in patients younger than 65 years. Conclusion. With the help of imaging, clinicians can specify a diagnosis and perform corresponding treatment in most cases. However, making a precise diagnosis of AAP within a short period is still challenging. Further research should be conducted to seek safer and more effective techniques to streamline clinicians’ work.